Factors Associated with the Behavior of Women of Childbearing Age in Early Detection of Cervical Cancer with Visual Inspection Examination Method Acetic Acid (IVA) in the Working Area of the Coconut Health Center West Bangka Regency in 2023 - Elvira, Elvira (Journal of Midwifery and Nursing, 2024)
Cervical cancer is a malignant process or growth of a malignant tumor on the cervix so that the surrounding tissue cannot perform its function properly. The purpose of this study was to look at the factors associated with the behavior of women of childbearing age in early detection of cervical cancer using the Acetic Acid Inspection (IVA) method in the Kelapa Health Center Work Area. This study was conducted using a cross sectional design and chi-square test with the results in the form of bivariate analysis and univariate analysis. The research population was women who visited the Kelapa health center in Januari-April 2023 with a total of 61 people. The research instrument used a questionnaire consisting of a questionnaire on WUS behavior, level of knowledge, attitudes, family support and support from health workers. The results of the study concluded that there was a relationship between knowledge (0.005), there was a relationship between attitudes (0.025), family support (0.018) and there was no relationship between support from health workers (0.856).